RECONSTRUCTION OF THE AUTHORITY TO DETERMINE THE CALCULATION OF STATE LOSSES RESULTING FROM CRIMINAL ACTS OF CORRUPTION - A. Muhajir; M. Iman Santoso; Hartanto; Lukman Hakim (Sekolah Tinggi Ilmu Hukum Awang Long, 2026)
The purpose of writing this dissertation is to determine the ideal authority regarding determining the calculation of state losses resulting from criminal acts of corruption. can be reconstructed ideally in the future. The research problem is based on the lack of harmony of norms that lead to the emergence of conflicting norms of laws and regulations related to the understanding of